Application of α-Syn Real-Time Quaking-Induced Conversion for Brain and Skin Specimens of the Chinese Patients With Parkinson’s Disease - Chen, Dong-Dong; Jiao, Ling; Huang, Yue; Xiao, Kang; Gao, Li-Ping; Chen, Cao; Shi, Qi; Dong, Xiao-Ping (Frontiers in Aging Neuroscience, 2022)
The real-time quaking induced conversion (RT-QuIC) assay has been developed and used as an in vitro diagnostic tool for PD. In this study, we established α-Syn RT-QuIC using recombinant human α-Syn as the substrate. All 5 brain homogenates of neuropathological PD cases and 13 skin homogenates of clinical PD cases showed positive results, while all the samples of negative controls remain negative. Meantime randomly selected 6 skin samples of PD cases and 6 skin samples of sCJD cases, which showed negative in opposite Prion RT-QuIC and α-Syn RT-QuIC. Our α-Syn RT-QuIC showed dose-dependent manner between the lag times and peak ThT fluorescent values. And the detecting limitation was about 10-7 dilution for brain tissues and 10-6 for skins. Those data indicate a reliable specificity and good sensitivity of the established α-Syn RT-QuIC in identifying and amplifying the misfolded α-Syn in brain and skin tissues of PD patients.